The Influence of Entrepreneurial Education, Opportunity, Orientation, and Advantage on Firm Performance - Erilia Kesumahati; Valentino Angeloi; Andina Fasha (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines how entrepreneurial education, opportunity orientation, and advantage interact to enhance entrepreneurs' performance in international markets. It aims to provide insights to strengthen SME competitiveness worldwide. Methodology/approach: This study employs a quantitative survey, distributing questionnaires to 101 active entrepreneurs in the export-import and cross-border business sectors. The data were analyzed using partial least squares structural equation modeling, with variables based on validated literature. Results: The findings show that entrepreneurial opportunities and entrepreneurial orientation significantly influence firm performance, whereas entrepreneurial education and entrepreneurial advantage do not, reinforcing prior studies on opportunity recognition, proactiveness, innovation, and risk-taking as global success factors. Conclusions: The findings of this study indicate that the performance of international firms is largely and consistently influenced by entrepreneurial opportunity recognition and entrepreneurial orientation, highlighting the crucial role of proactive, innovative, and risk-taking behaviors in achieving superior outcomes in international markets. In contrast, entrepreneurial education and entrepreneurial advantage do not show a statistically significant direct effect on international firm performance, suggesting that formal knowledge acquisition and perceived competitive strengths may contribute only indirectly or through other mediating factors rather than exerting an immediate impact. Limitations: This study is limited by its small sample size and focus on entrepreneurs already active in international business. Future research should consider additional factors, such as market access, digitalization, and organizational culture. Contributions: This study highlights the key drivers of international firm performance and offers guidance for entrepreneurs, educators, and policymakers to enhance competitiveness, improve curricula, and shape supportive policies.